Legal Protection of Policyholders for Claim Issues Insurance coverage based on positive Indonesian law - Andika Jinaratana; Yofi Permatasari; Meliana Kartika H (Asian Journal of Social and Humanities, 2023)
This paper reviews the legal protection for insurance policyholders according to Indonesian positive law. This is aimed at increasing our understanding of the concept of insurance and how legal protection is for policyholders for problems with claims for insurance coverage and how the liability of the insurance company as the insurer is towards the insured, namely the policyholder. Insurance policy holders are generally individuals, many of whom are people who are unfamiliar with the law and must be confronted with insurance companies, so based on this it is important for positive law to provide legal protection for insurance policy holders from violations of the law by insurance companies and of course all forms included law violations must be held accountable.